Lands of wonder Europe to Africa - Eder, Stephen (Great national parks of the world, 2000)
Take a thrilling journey to four of the greatest natural treasures of Europe and Africa. Walk along the misty shores of Ireland's rocky northern coast to experience the legendary Giants's Causeway. Search for elusive mountain gorillas in Uganda's lush Impenetrable Forest. Climb the stunning snow-capped peaks of Italy's timeless Alps to discover the regal ibex in Gran Paradiso National Park. Behold the spectacle of thundering herds of migrating wildebeest, zebra and gazelle on Africa's fabled Serengeti Plains - wildlife as far as the eye can see!